2018
DOI: 10.1109/tthz.2018.2872413
|View full text |Cite
|
Sign up to set email alerts
|

Terahertz Transition-Edge Sensor With Kinetic-Inductance Amplifier at 4.2 K

Abstract: Different terrestrial terahertz applications would benefit from large-format arrays, operating in compact and inexpensive cryocoolers at liquid helium temperature with sensitivity, limited by the 300-K background radiation only. A voltage-biased Transition-Edge Sensor (TES) as a THz detector can have sufficient sensitivity and has a number of advantages important for real applications as linearity of response, high dynamic range and a simple calibration, however it requires a low-noise current readout. Usually… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…Some thermal THz sensors have been reported to achieve ultrahigh sensitivity by cooling to extremely low temperatures to suppress thermal noise. [98][99][100] The detection principles of photonics can be classified into linear and nonlinear responses. In the linear mechanism, sensors are designed to absorb and emit the same energy levels as the THz light using quantum wells and Landau levels.…”
Section: Sensor Typementioning
confidence: 99%
“…Some thermal THz sensors have been reported to achieve ultrahigh sensitivity by cooling to extremely low temperatures to suppress thermal noise. [98][99][100] The detection principles of photonics can be classified into linear and nonlinear responses. In the linear mechanism, sensors are designed to absorb and emit the same energy levels as the THz light using quantum wells and Landau levels.…”
Section: Sensor Typementioning
confidence: 99%
“…The transition edge sensor requires tuning to operate at that particular temperature and requires integrated amplifiers [52]. Recently, a terahertz transition edge sensor has been coupled with a kinetic inductance amplifier (instead of the usual superconducting quantum interference device amplifier) to provide a linear device with high dynamic range operating at 4.2 K. The NEP is ≈ 5 × 10 −14 W Hz −1/2 [53].…”
Section: Semiconductor Bolometer (Class A5cmentioning
confidence: 99%
“…For millimeter and sub-millimeter wave detection, many groups have worked on antenna-coupled micro and nano bolometers, mostly with low T c superconductors [11], [12]. Recently, Kuzmin et al reported an antennacoupled, voltage biased transition edge sensor for 1-6 THz [13], where the superconducting material is 5 nm-thin NbN, and the operating temperature of the device is 4.2 K. Also, Hammer et al [14] reported a THz detector based on spiral antenna coupled YBCO microbolometer with responsivity of 190 V/W across the frequency range of 330 GHz to 1.63 THz. Log-spiral [15], [16], slot antenna [11], and sinuous antenna [17] are different types of antennas which are mostly used in this era.…”
Section: Introductionmentioning
confidence: 99%